A Systemic Approach To The Study Of The Clause As Exchange In Imperative and Exclamative Clauses In English and Arabic - Dr. Hala K. Najim (PROSPECTIVE RESEARCHES, 2023)
The aim of this paper is to describe the clause as exchange in English and Arabic imperative and exclamative clauses. The model adopted for this paper is Systemic Functional Grammar as presented in Halliday (1994). An attempt is made to study the interpersonal metafunction in the mood system. The paper draws a conclusion that the Hallidayan approach can be applied to some extent to Arabic imperatives and exclamatives. In both English and Arabic, the interpersonal metafunction is realized in the mood system. Certain points of similarity and difference are also highlighted.